2011
DOI: 10.1007/s00134-011-2368-0
|View full text |Cite
|
Sign up to set email alerts
|

New insights into weaning from mechanical ventilation: left ventricular diastolic dysfunction is a key player

Abstract: Our findings suggest that LV diastolic dysfunction is significantly associated with weaning outcome in critically ill patients with preserved LV systolic function. An E/E m ratio greater than 7.8 may identify patients at high risk of weaning failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
91
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 41 publications
(68 reference statements)
4
91
0
2
Order By: Relevance
“…Among these conditions are myocardial ischemia and congestive heart failure. 1 The decrease in ventilator support during a spontaneous breathing trial (SBT) can increase preload, afterload, and catecholamine release [2][3][4][5] and possibly exacerbate underlying cardiac dysfunction, resulting in pulmonary edema and unsuccessful weaning. These processes may also cause myocardial ischemia, 6 leading to pulmonary edema related to the increased transmural pulmonary artery occlusion pressure associated with decreased myocardial compliance.…”
mentioning
confidence: 99%
“…Among these conditions are myocardial ischemia and congestive heart failure. 1 The decrease in ventilator support during a spontaneous breathing trial (SBT) can increase preload, afterload, and catecholamine release [2][3][4][5] and possibly exacerbate underlying cardiac dysfunction, resulting in pulmonary edema and unsuccessful weaning. These processes may also cause myocardial ischemia, 6 leading to pulmonary edema related to the increased transmural pulmonary artery occlusion pressure associated with decreased myocardial compliance.…”
mentioning
confidence: 99%
“…The result indicated that LV diastolic dysfunction is significantly associated with weaning outcome in critically ill patients with preserved LV systolic function. An E/E a ratio greater than 7.8 may identify patients at high risk of weaning failure [17]. Schifelbain et al conducted randomized crossover clinical trial of 24 patients to analyze changes in cardiac function, using Doppler echocardiogram, in critical patients during weaning from MV.…”
Section: Discussionmentioning
confidence: 99%
“…The main result is presented in Fig. 2 of their study [1]. Among the 23 patients without LV diastolic dysfunction before the spontaneous breathing trial (SBT), eight failed to be weaned (35%), whereas among the 20 patients with moderate to severe LV diastolic dysfunction, 80% failed to be weaned.…”
mentioning
confidence: 99%
“…In the December 2011 issue of Intensive Care Medicine, Papanikolaou and coworkers [1] reported their investigation into the diagnostic performance of echocardiography in predicting the outcome of weaning, and especially the role of left ventricular (LV) diastolic function in weaning failure. The main result is presented in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation